The Influence of Reading Strategies on Comprehension Skills in English Language Learners - Hilmi, Muhammad (Lembaga Yasin AlSys, 2025)
Reading ability is a fundamental skill in language mastery, especially in English language learning. However, many students in Indonesia experience difficulties in understanding English texts due to a lack of effective reading strategies. This issue forms the basis of a study to evaluate the impact of reading strategies on improving students' reading comprehension. The aim of this research is to analyze how reading strategies can assist students in understanding English texts. The research employs a descriptive quantitative method, involving 50 students divided into experimental and control groups. Data were collected through pre-tests and post-tests and analyzed using normality and homogeneity statistical tests, as well as a T-test to measure the effectiveness of reading strategies. The results showed that the experimental group, which used reading strategies, demonstrated a significant improvement in comprehension compared to the control group. These findings suggest that the application of appropriate reading strategies can enhance reading comprehension skills, particularly for students learning English as a foreign language.